2004
DOI: 10.1038/sj.eye.6700664
|View full text |Cite
|
Sign up to set email alerts
|

Interocular asymmetry of visual field defects in primary open angle glaucoma and primary angle-closure glaucoma

Abstract: Aim To compare the interocular asymmetry in visual field loss of patients with primary open-angle (POAG) and primary angle-closure glaucoma (PACG). Methods Subjects entering a prospective, randomised, controlled trial of intraoperative 5-fluorouracil in glaucoma surgery in Singapore were included. Preoperative visual field testing was performed using automated white-on-white perimetry (24-2 test pattern, threshold program, Mk II, Model 750, ZeissHumphrey, San Leandro, CA, USA). A minimum of two tests were requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 13 publications
1
17
1
Order By: Relevance
“…However, another study by Wang et al 4 had a predominance of male patients in the POAG group (3:1) as compared with almost equal representation in the PACG group. In a study by Rhee et al 9 , the maximum IOPs were higher in PACG group (31.9mm Hg) vs POAG group (25.1 mmHg) and the mean IOP at the time of visual fields test was higher in the POAG group (22.5 +/-4.8 mmHg) vs PACG group (17.2 +/-5.5 mmHg).In our study, the mean IOP at the time of diagnosis, in the PACG group was higher being 30.06 +/-0.5, while the mean IOP in the POAG group was 27.05 +/-0.5mmHg.Caprioli et al 10 reported that IOPs were consistently higher in eyes with diffuse field loss compared to eyes with localised field loss.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, another study by Wang et al 4 had a predominance of male patients in the POAG group (3:1) as compared with almost equal representation in the PACG group. In a study by Rhee et al 9 , the maximum IOPs were higher in PACG group (31.9mm Hg) vs POAG group (25.1 mmHg) and the mean IOP at the time of visual fields test was higher in the POAG group (22.5 +/-4.8 mmHg) vs PACG group (17.2 +/-5.5 mmHg).In our study, the mean IOP at the time of diagnosis, in the PACG group was higher being 30.06 +/-0.5, while the mean IOP in the POAG group was 27.05 +/-0.5mmHg.Caprioli et al 10 reported that IOPs were consistently higher in eyes with diffuse field loss compared to eyes with localised field loss.…”
Section: Discussionmentioning
confidence: 95%
“…Glaucoma diagnosis and monitoring requires assessment of structure and function of the optic nerve, and visual field analysis by perimetry is considered the gold standard for functional assessment of optic nerve 3 . Visual field studies have revealed rate of uniocular visual field loss being 2-3 times higher in cases of primary angle closure glaucoma and greater interocular asymmetry in visual field loss in patients with PACG 4,5 . This suggests a difference in the pathophysiological process of the two diseases.…”
Section: Introductionmentioning
confidence: 99%
“…This position may be particularly advantageous for patients with glaucoma to prevent the increase in IOP when head rotation 45 o laterally in prone position is used and the more severely affected eye is kept in the upper position. The asymmetry of visual fi eld loss between eyes in primary angle closure glaucoma (PACG) and primary open angle glaucoma (POAG) was described by Wang et al 10 . A more marked thinning of the neuroretinal nerve fi ber layer in the eye with the higher IOP has also been described in normal-tension glaucoma patients 11 .…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] In normal-tension glaucoma (NTG), other factors such as vascular abnormalities may also be involved. Pressure-dependent damage was thought to be the major component causing chronic angle-closure glaucoma (CACG), whereas primary open-angle glaucoma (POAG; high-tension glaucoma, HTG) is more likely to have a mixture of pressure-dependent and pressure-independent etiologies.…”
mentioning
confidence: 99%
“…[1][2][3] In normal-tension glaucoma (NTG), other factors such as vascular abnormalities may also be involved. 3,[10][11][12] Population-based studies in Asia showed that unilateral visual field loss was about 2 or 3 times more often found in CACG than in POAG. In an extensive literature review of 1008 NTG patients, Levene 10 concluded that unilateral field loss was more frequently seen in NTG than in HTG.…”
mentioning
confidence: 99%